(untitled) (Jurnal Manajemen Bisnis, 2023)
This study focuses on Lazada App Users, aiming to measure how much Customer Satisfaction Role in mediating the effect of Mobile Shopping Service Quality on Customer Loyalty. Using the non-probability sampling method, namely purposive sampling, 251 samples were selected. Data collection is carried out by non-probability sample method with quantitative method approach. SEM (Stuctural Equation Modelling) analysis model with test calculations using the LISREL software program version 8.80. The effectiveness of mobile shopping experience according to the results of this study shows that Mobile Shopping Service Quality has a positive and significant effect on customer satisfaction. Mobile Shopping Service Quality does not have a positive and significant effect on customer loyalty. Customer Satisfaction has a positive and significant effect on Customer Loyalty. Mobile Shopping Service Quality has a positive and significant effect on customer loyalty mediated by Customer Satisfaction. And the most influential dimension of MS-SQ is Responsiveness. The study suggests workable strategies to increase effectiveness in increasing loyalty in the m-commerce industry and extends the loyalty research model built from MS-SQ.